Analisis Perencanaan Strategi Pemasaran Pada Teh 2M - Sari, Dian; Masniar, Masniar; Amri, Irman; Gani, Mardiah; Hahury, Sanny (Universitas Muhammadiyah Sorong, 2023)
Marketing strategy is a management structured to accelerate solving marketingproblems and making strategic decisions. Marketing strategy has an important role inachieving business success, therefore the marketing sector plays a major role in realizingstrategic marketing plans to increase product sales. This can be done, if the company wants tomaintain and increase sales of the products or services they produce. By implementing anaccurate marketing strategy through the use of opportunities to increase sales, the company'sposition in the market can be improved or maintained. CV. Harum Manis is the only factorythat produces packaged tea drinks in West Papua. This local product from Sorong is actuallyless popular when compared to packaged tea from outside the Sorong area. The researchmethod used is SWOT analysis. The Internal Condition on the Strength Factor is worth 2.00and the Weakness Factor is worth 1.90, while the External Condition on the OpportunityFactor is 2.19, while the Threat Factor is 1.60. The results of the SWOT analysis show thatCV HARUM MANIS is in the Quadrant I WO (Weakness – Opportunity) position. Judgingfrom the position of the company is in Quadrant I where Quadrant I is a very profitablesituation. Where companies in this quadrant have opportunities and strengths so they can takeadvantage of existing opportunities.